POTENSI ARKEOLOGI LANSKAP BAWAH AIR INDONESIA - Shinatria Adhityatama; Ajeng Salma Yarista (KALPATARU, 2019)
Indonesia has a great potential to be a country-wide laboratory of underwater landscape study. This is due to the fact that its two main contingents, Sunda and Sahul, had been experiencing sea level rise event in the late of ice age , in which intersectedcrosses the timeline of prehistoric human migration. Even though Indonesian ocean preserves the richness of underwater resources, including archaeological data, the study itself has not been touched by many. This paper will focus in two objectives: 1) Reconstructing paleo-river model and; 2) Potential prehistoric remnants in Misool Islands caves. The method used includes a field survey , by diving and data brackets by using sub-bottom profiler. Besides, we also conducted literature reviews.The results of this study indicate that the Sunda and Sahul Exposures are likely to be inhabited by humans, but at this time the remains have sunk on the seabed. It is hoped that this study can be the basis and motivation for future archeological research such as prehistoric human settlements and migration in a submerged landscape environment. Indonesia memiliki potensi yang besar untuk menjadi sebuah laboratorium penelitian lanskap bawah air. Gagasan ini didasarkan pada fakta bahwa dua kontingen yang membentuk Indonesia, Paparan Sunda dan Sahul, mengalami perubahan air laut pada akhir zaman es yang bersinggungan dengan migrasi manusia prasejarah. Walaupun lautan Indonesia menyimpan kekayaan alam, termasuk data arkeologi, penelitian tentang lanskap bawah laut belum banyak disentuh. Studi ini bertujuan untuk membahas dua hal: 1) rekonstruksi model sungai purba dan ;2) potensi peninggalan jejak prasejarah di gua bawah air di Pulau Misool. Metode yang digunakan adalah melakukan survei lapangan, dengan melakukan penyelaman dan perkeman data menggunakan alat akustik sub-bottom profiler, selain itu kami juga melakukan kajian dan review pustaka.Hasil studi ini menunjukkan bahwa Paparan Sunda dan Sahul kemungkinan besar telah dihuni oleh manusia namun pada saat ini peninggalannya telah tenggelam di dasar laut, diharapkan kajian ini dapat menjadi dasar dan motivasi untuk riset arkeologi mendatang seperti hunian dan migrasi manusia prasejarah pada lingkungan lanskap yang tenggelam.